Quality Of Service (QOS) Analysis on LTE Networks Time Division Duplex and Frequency Division Duplex Technology - Rizki Aulia; Dikky Chandra; Yulian Mirza; Nasrul; Miro Dhino (International Journal of Wireless And Multimedia Communications, 2024)
Quality of service is a method of measuring a network and attempts to define a characteristic used to provide good service. The increasing use of mobile technology has a rapid impact on the development of technology and information. These developments relate to the use of customized information and communication services in a direct, practical and effective manner. In response to these issues, researchers are interested in conducting research by looking at the parameters of Time Division Duplex (TDD) technology at a frequency of 2300 MHz and Frequency Division Duplex (FDD) at a frequency of 900 MHz on the download service. The results of quality of service measurements on LTE networks are carried out in real time in the field by comparing each QoS parameter against a predetermined path from the eNodeB point based on RSRP and SINR with different conditions. In both TDD and FDD technology. The effect of RSRP on Quality of Service parameters in each cell measured. One of them is PCI 328, when the RSRP condition is measured - 80 dBm, the throughput value is 9466.29 Kbps, latency 0.84 ms, jitter 0.028 ms and packet loss 0%. Conversely, when the RSRP condition is measured - 100 dBm, the throughput is 4084.16 Kbps, latency 1.68 ms, jitter 0.059 ms and packet loss 0.50%. Then the effect of SINR on Quality of Service parameters in 2 different modulations is seen in each cell measured. One of them is PCI 328, when the SINR condition is measured at 20 dBm, the throughput value is 9074.99 Kbps, latency 0.86 ms, jitter 0.034 ms and packet loss 0%. Conversely, when the SINR condition measured 12 dB then the throughput is 4239.58 Kbps, latency 0.88 ms, jitter 0.027 ms and packet loss 0.03%. Based on the results obtained the throughput value of LTE TDD has a better value on the download service and has a better throughput value.